Characterization of a Cohort of Patients With LIG4 Deficiency Reveals the Founder Effect of p.R278L, Unique to the Chinese Population - Luo, Xianze; Liu, Qing; Jiang, Jinqiu; Tang, Wenjing; Ding, Yuan; Zhou, Lina; Yu, Jie; Tang, Xuemei; An, Yunfei; Zhao, Xiaodong (Frontiers in Immunology, 2021)
DNA ligase IV (LIG4) deficiency is an extremely rare autosomal recessive primary immunodeficiency disease caused by mutations in LIG4. Patients suffer from a broad spectrum of clinical problems, including microcephaly, growth retardation, developmental delay, dysmorphic facial features, combined immunodeficiency, and a predisposition to autoimmune diseases and malignancy. In this study, the clinical, molecular, and immunological characteristics of 15 Chinese patients with LIG4 deficiency are summarized in detail. p.R278L (c.833G>T) is a unique mutation site present in the majority of Chinese cases. We conducted pedigree and haplotype analyses to examine the founder effect of this mutation site in China. This suggests that implementation of protocols for genetic diagnosis and for genetic counseling of affected pedigrees is essential. Also, the search might help determine the migration pathways of populations with Asian ancestry.